2020
DOI: 10.1155/2020/8849252
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Thrombosis in the Setting of Malignancy: Case Report and Review of the Literature

Abstract: Cerebral venous thrombosis (CVT) is a rare condition that can be difficult to diagnose due to its vague and nonspecific symptoms. It is even more unusual to identify CVT in association with malignancy. Given the rarity of this disease, treatment and management of CVT in the setting of malignancy is not well defined. This case report and review of the literature addresses the epidemiology, pathophysiology, and medical treatment for malignancy-related CVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…CVST is an uncommon type of VTE [1][2][3][4]. The incidence of CVST was about 0.3-4% in cancer patients, with cancer increasing risk for CVST roughly 5-fold [5,7]. Extracranial VTE events such as deep venous thrombosis and pulmonary embolism have been widely reported in HGG; however, the incidence of CVST in HGG patients is not well established in the literature [4,5].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…CVST is an uncommon type of VTE [1][2][3][4]. The incidence of CVST was about 0.3-4% in cancer patients, with cancer increasing risk for CVST roughly 5-fold [5,7]. Extracranial VTE events such as deep venous thrombosis and pulmonary embolism have been widely reported in HGG; however, the incidence of CVST in HGG patients is not well established in the literature [4,5].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CVST was about 0.3-4% in cancer patients, with cancer increasing risk for CVST roughly 5-fold [5,7]. Extracranial VTE events such as deep venous thrombosis and pulmonary embolism have been widely reported in HGG; however, the incidence of CVST in HGG patients is not well established in the literature [4,5]. According to a recent study, the incidence of CVST in glioblastoma multiforme patients was reported to be 7.4% [3].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations